Land Mafia Practices in Undermining National Resilience - Agustyarsyah (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
Land mafia practices often involve document forgery, engineered lawsuits in courts to gain land rights, and conspiratorial acts in authentic deeds or informational letters with the involvement of public officials. These practices contradict the principles of economic development that prioritize sustainability, environmental protection, and long-term social welfare. This study aims to identify and analyze land mafia practices and their impacts, which pose a threat to national resilience. The research employs a qualitative method with a case study approach, focusing on exploring the causes and consequences to uncover root problems and hidden issues. The findings highlight two key points: (1) the need for land justice to ensure legal certainty and fairness for society, and (2) the necessity for the state to strengthen its capacity to protect itself from threats across various sectors (asta gatra), enabling effective anticipation of land mafia actions that could undermine national resilience.